2014
DOI: 10.5487/tr.2014.30.1.019
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone Suppresses LXRα-Induced Hepatic Lipogenic Gene Expression through AMPK/Sirt1 Pathway Activation

Abstract: Licochalcone (LC), a major phenolic retrochalcone from licorice, has anti-inflammatory activity. This study investigated the effects of licochalcone A (LCA) and licochalcone E (LCE) on Liver X receptor-α (LXRα)-mediated lipogenic gene expression and the molecular mechanisms underlying those effects. LCA and LCE antagonized the ability of LXRα agonists (T0901317 or GW3965) to increase sterol regulatory element binding protein-1c (SREBP-1c) expression and thereby inhibited target gene expression (e.g., FAS and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Our result exhibited that Q3GA dose‐dependently decreased SREBP‐1c and its downstream key gene FAS mRNA expression in in vitro and in vivo NAFLD models. In line with the present study, some flavonoids have given direct evidence that they downregulate SREBP‐1c involved in lipogenesis and ameliorating NAFLD disease . Surprisingly, we found that no change in mRNA expression of LXR‐α occurred compared with the model group.…”
Section: Discussionsupporting
confidence: 92%
“…Our result exhibited that Q3GA dose‐dependently decreased SREBP‐1c and its downstream key gene FAS mRNA expression in in vitro and in vivo NAFLD models. In line with the present study, some flavonoids have given direct evidence that they downregulate SREBP‐1c involved in lipogenesis and ameliorating NAFLD disease . Surprisingly, we found that no change in mRNA expression of LXR‐α occurred compared with the model group.…”
Section: Discussionsupporting
confidence: 92%
“…After a two-step proteolytic cleavage, SREBPs are competent to transactivate genes involved in lipid synthesis (19,31). Sterol depletion and ethanol exposure have been reported to increase SREBP-dependent Lipin1 expression (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…AMP-activated protein kinase (AMPK), which is recognized as a major regulator of fat metabolism, is a key sensory enzyme controlling energy metabolism ( 12 , 13 ). When AMPK is activated by phosphorylation by the upstream AMPK kinase, it functions as a cellular energy sensor through the regulation of fatty acid and glucose homeostasis ( 14 , 15 ). AMPK also induces inactivation by phosphorylating ACC, an important enzyme for fatty acid oxidation and biosynthesis ( 11 , 16 ).…”
Section: Introductionmentioning
confidence: 99%